Pandemic management: Analysis of availability and relevance of surveillance indicators by COVID-Task-Forces in the German federal state of Lower Saxony - Nicolás Reinoso Schiller; Karina Usipbekova; Katja Hille; Johannes Dreesman; Kjell Schwarz; Karin Reimers; Fabian Feil; Simone Scheithauer (Elsevier, 2023)
summary: Background: Locally, the introduction of measures during times of a pandemic emergency is embodied in a pandemic containment plan created by the Robert Koch Institute in 2017. In addition to central indicators such as incidence rates and number of deaths, various indicators are used at the local level to assess the pandemic situation. So far, there hasn't been analyses of the availability and perceived relevance of the surveillance indicators used to manage the SARS-CoV-2 pandemic by the local German pandemic task forces. Aim: This study examined whether local decision-makers had access to surveillance-related indicators in a way that they could be used to make informed decisions in response to the pandemic situation. Methods: A cross sectional study was conducted, using an online questionnaire developed by experts of The Public Health Agency of Lower Saxony and The University Medical Center Göttingen (UMG). All local COVID-19 task forces of the German state of Lower-Saxony were enrolled in the study. Findings: The surveillance indicators assessed by survey respondents as most available and relevant are included under the German Infection Protection Act (IfSG). In contrast, the indicators that are not bound by the IfSG have a significantly lower availability and an inconsistent assessment of relevance. Conclusion: Against the background of efficiency, it seems central to be able to reliably provide the highly weighted surveillance indicators. Nevertheless, the relevance assessment gap between the indicators embedded in the IfSG and the ones that are not may be explained by cognitive processes such as anchoring bias. The collection and use of indicators to assess the pandemic situation and to evaluate measures should be the subject of continuous multidisciplinary discussions.